Caulerpa peltata Methyl Esters as A Renewable Source of Energy - Annam Renita, A.; Joshua Amarnath, D.; Kirubagaran, R.; Magesh Peter, D. (Asian Journal of Chemistry, 2012)
In this paper, ten species of macroalgae comprising of four green algae, three brown algae and three red algae collected from Gulf of Mannar were evaluated for their lipid content and this paper strives to suggest an alternate to diesel fuel from bio-diesel derived from the green macro algae, Caulerpa peltata. Biodiesel characterization was based on ASTMD6751 and the glycerine content and flash point was found to be little bit higher than the standards. Kinematic viscosity, iodine value, neutralization value were within the permissible limits.